National accounts digest 2000-2003 (CCS [Georgetown]GY, 2007)
Provides statistics on the economic conditions and performance of the CARICOM region over a specific period as reflected in the Gross Domestic Product of its Member States.
Keywords: NATIONAL ACCOUNTS